Non-invasive measurement of liver iron concentration using 3-Tesla magnetic resonance imaging: validation against biopsy. - d’Assignies, Gaspard; Paisant, Anita; Bardou-Jacquet, Edouard; Boulic, Anne; Bannier, Elise; Lainé, Fabrice; Ropert, Martine; Morcet, Jeff; Saint-Jalmes, Hervé; Gandon, Yves; d'Assignies, Gaspard (European Radiology, 2018)
Objectives: To evaluate the performance and limitations of the R2* and signal intensity ratio (SIR) methods for quantifying liver iron concentration (LIC) at 3 T.Methods: A total of 105 patients who underwent a liver biopsy with biochemical LIC (LICb) were included prospectively. All patients underwent a 3-T MRI scan with a breath-hold multiple-echo gradient-echo sequence (mGRE). LIC calculated by 3-T SIR algorithm (LICSIR) and by R2* (LICR2*) were correlated with LICb. Sensitivity and specificity were calculated. The comparison of methods was analysed for successive classes.Results: LICb was strongly correlated with R2* (r = 0.95, p < 0.001) and LICSIR (r = 0.92, p < 0.001). In comparison to LICb, LICR2* and LICSIR detect liver iron overload with a sensitivity/specificity of 0.96/0.93 and 0.92/0.95, respectively, and a bias ± SD of 7.6 ± 73.4 and 14.8 ± 37.6 μmol/g, respectively. LICR2* presented the lowest differences for patients with LICb values under 130 μmol/g. Above this value, LICSIR has the lowest differences.Conclusions: At 3 T, R2* provides precise LIC quantification for lower overload but the SIR method is recommended to overcome R2* limitations in higher overload. Our software, available at www.mrquantif.org , uses both methods jointly and selects the best one.Key Points: • Liver iron can be accurately quantified by MRI at 3 T • At 3 T, R2* provides precise quantification of slight liver iron overload • At 3 T, SIR method is recommended in case of high iron overload • Slight liver iron overload present in metabolic syndrome can be depicted • Treatment can be monitored with great confidence.